Pemusnahan Barang Sitaan Narkotika Rangka Pencegahan Penyimpangan Peredaran Kembali Barang Sitaan di Masyarakat (Studi Kejaksaan Negeri Belawan) - Aisyah Aisyah; Alpi Sahari Alpi Sahari; T. Erwinsyahbana T. Erwinsyahbana (DOKTRINA: JOURNAL OF LAW, 2023)
The purpose of this study is to find out about the authority of the Prosecutor as executor in carrying out the destruction of confiscated goods resulting from criminal acts and the obstacles in carrying out the destruction of confiscated narcotics crimes, as well as the perspective of destroying confiscated goods in order to prevent the re-circulation of confiscated narcotics crimes in society. The research method is normative legal research, which uses secondary data sources with an emphasis on theoretical and qualitative analysis. The results of the study found acts of destroying evidence of narcotics according to Article 26 paragraph 1 of Government Regulation No. 40 of 2013 concerning Implementation of Law No. 35 of 2009 concerning Narcotics, law enforcement agencies that are allowed to destroy narcotic evidence are BNN investigators and POLRI investigators, and prosecutors. Barriers to the destruction of confiscated goods for narcotics crime there are 5 (five) factors, namely; the legal factors themselves, law enforcement factors, facilities or facilities factors, community factors. The Belawan District Prosecutor's Office has taken preventive action, namely control is carried out to prevent the possibility of undesirable things from happening in the future, preventive or preventive actions are carried out by the Belawan District Prosecutor's Office as the executor of the Court Decision, aiming to protect against bad things that may occur, such as loss or misuse of confiscated narcotics.